Complete mitochondrial genome of Kjellmaniella crassifolia (Laminariaceae, Phaeophyceae): Laminaria and Saccharina are distinct genus. (1st November 2016) - Zhang, Lei; Wang, Xumin; Liu, Tao; Wang, Guoliang; Chi, Shan; Liu, Cui; Wang, Haiyang
Abstract: The kelp Kjellmaniella crassifolia is one of the most important economic resources, which is widely distributed in Japan and has now been introduced to coastal areas in China's Shandong Province for cultivation. In this study, we present the complete mitochondrial genome of K. crassifolia . The genome is characterized as a circular molecule of 37, 627 bp in length with an overall A + T content of 64.81%. The mitogenome contains three ribosomal RNA genes (rRNA), 24 transfer RNA genes (tRNA), 35 protein-coding genes, and three conserved open reading frames (ORFs). Most genes are encoded on the H-strand and 11 pairs of overlapping genes are identified with the overlap size from 1 to 16 bp. The gene content and organization of mitogenome for K. crassifolia is identical to those for Saccharina, Laminaria, Undaria, and Costaria . Phylogenetic analysis based on 35 mitochondrial protein-coding genes clearly proves that Laminaria and Saccharina are distinct genus identified by Kjellmaniella . The present study provides new molecular data for further studies on evolutionary relationship within Phaeophyceae.